Holistic identification and assessment of environmental risks of arable land use in two grain producing areas of China - Guanyi Yin (Taylor & Francis Group, 2020)
Taking two typical grain producing areas of southern (Dongting Lake Region) and northern China (Shandong Province) as examples, this study used fault tree analysis and parametric estimation to provide a comparative analysis for environmental risks of intensive arable land use. The results show that (1) in the risks of eutrophication, toxicity, soil structure, greenhouse effect and air pollution, the greenhouse effect was the most prominent with the highest discharge; (2) the Dongting Lake Region discharged less pollutants annually than did Shandong Province, while surpassing Shandong in cumulative pollutant discharge in 2007-2018; (3) the spatial distribution of environmental risk in the Dongting Lake Region was mostly concentrated in the northern area, whereas that in Shandong Province displayed a scattered pattern; (4) in the Dongting Lake Region, Yueyang, Changde, and Yiyang were high environmental risk cities in 2007-2018, whereas in Shandong Province, Zaozhuang, Heze, Liaocheng, and Dezhou exhibited higher comprehensive environmental risk indexes in 2007-2008, while Rizhao replaced them in 2018. The results indicated that ago-production material use must be controlled, reasonable zoning for areas posing environmental risks must be employed and cities with high environmental risk must be dynamically monitored to prevent the intensification of environmental risks of arable land use.